2001
DOI: 10.1016/s0022-5096(01)00042-4
|View full text |Cite
|
Sign up to set email alerts
|

Rate and state dependent friction and the stability of sliding between elastically deformable solids

Abstract: We study the stability of steady sliding between elastically deformable continua using rate and state dependent friction laws. That is done for both elastically identical and elastically dissimilar solids. The focus is on linearized response to perturbations of steady-state sliding, and on studying how the positive direct e ect (instantaneous increase or decrease of shear strength in response to a respective instantaneous increase or decrease of slip rate) of those laws allows the existence of a quasi-static r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
639
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 574 publications
(672 citation statements)
references
References 52 publications
30
639
1
2
Order By: Relevance
“…Rice et al [2001] derived a regularized expression based on the friction laws of Dieterich [1979] and Ruina [1983] which overcomes this limitation. Assuming for simplicity that there are no state evolution effects, which may be appropriate for high temperature sliding of granite surfaces [Blanpied et al, 1998], solid plug shear tractions t p are equal to…”
Section: Motion Of the Solid Plugmentioning
confidence: 99%
“…Rice et al [2001] derived a regularized expression based on the friction laws of Dieterich [1979] and Ruina [1983] which overcomes this limitation. Assuming for simplicity that there are no state evolution effects, which may be appropriate for high temperature sliding of granite surfaces [Blanpied et al, 1998], solid plug shear tractions t p are equal to…”
Section: Motion Of the Solid Plugmentioning
confidence: 99%
“…During the following interseismic period, the locked region of patch A shrinks by penetration of creep from the surrounding areas, which occurs due to stress concentration at the boundary between creeping and locked regions (e.g., Tse and Rice, 1986;Lapusta et al, 2000). Earthquake rupture nucleates when the creeping region within patch A becomes comparable to the nucleation size estimates (Rice and Ruina, 1983;Rice et al, 2001;Rubin and …”
mentioning
confidence: 99%
“…(Turcotte and Schubert, 1982), and can yield viscosity on the fault plane (Byerlee, 1968). Rice et al (2001) discussed that rate-and state-dependent friction in thermally activated processes allows creep slippage at asperity contacts on the fault plane. Scholz (1990) suggested that the friction melts would present significant viscous resistance to shear and thus inhibit continued slip.…”
Section: Viscositymentioning
confidence: 99%